2004
DOI: 10.1117/12.544716
|View full text |Cite
|
Sign up to set email alerts
|

Gold standards and expert panels: a pulmonary nodule case study with challenges and solutions

Abstract: Introduction: Comparative evaluations of reader performance using different modalities, e.g. CT with computer-aided detection (CAD) vs. CT without CAD, generally require a "truth" definition based on a gold standard. There are many situations in which a true invariant gold standard is impractical or impossible to obtain. For instance, small pulmonary nodules are generally not assessed by biopsy or resection. In such cases, it is common to use a unanimous consensus or majority agreement from an expert panel as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…The findings of these expert panels may be combined and permuted (in a logical and scientifically sound manner) to obtain a series of non-unique “truth” sets against which the performance of the system under consideration may vary substantially (11–13). …”
Section: Introductionmentioning
confidence: 99%
“…The findings of these expert panels may be combined and permuted (in a logical and scientifically sound manner) to obtain a series of non-unique “truth” sets against which the performance of the system under consideration may vary substantially (11–13). …”
Section: Introductionmentioning
confidence: 99%
“…Surrogate end points reduce the cost of follow-up, reduce the challenge of low prevalence, or both. The shortcomings of surrogate end points are that they do not follow a patient to a clinical outcome, are subject to appreciable variability that needs to be addressed (106,107), and may be highly disease and/or technology specific. Several of the workshop speakers indicated that this topic should get more attention.…”
Section: Topics Deserving More Research and Attentionmentioning
confidence: 99%
“…3,4 Picking a single favorable "truth" can also help superficially improve results. 5 In addition, there are algorithms that attempt to reconcile the differences between segmentations to get one "ground truth." 6,7 The problem with the algorithms is that once the "ground truth" is established, the differences in the segmentations from which the ground truth was derived are lost.…”
Section: Introductionmentioning
confidence: 99%